J16 Exploring the acceptability and key components for success of a 12 month physical activity intervention in early to mid-stage Huntington's disease. (12th September 2022) - Drew, Cheney; Hamana, Katy; Williams-Thomas, Rhys; Playle, Rebecca; Busse, Monica; Quinn, Lori
Abstract : Background: The PACE-HD trial investigated the feasibility of conducting a randomised controlled trial of a 12-month physical activity intervention delivered by physiotherapists. Aim: To conduct a process evaluation of the PACE-HD intervention to specifically assess intervention components affecting acceptability and fidelity of intervention delivery. Method: Intervention delivery and acceptability was assessed via an end of study questionnaire completed by participants randomised to receive the intervention as part of an evaluation framework. Questionnaires required respondents to rate items relating to various intervention components on a scale from 1 [strongly disagree] to 5 [strongly agree] and additional open text questions. Scores of 4 and above were rated as positive. Results: Twenty participants completed the questionnaire. Responses regarding the support of therapists were largely positive (99%) with full enjoyment of and satisfaction with coach-led sessions (100%), plus high enjoyment of self-supported sessions (85%). Only some (65%) participants reported that the provided workbook aided goal setting and its use was not frequent. Most (80%) participants used the Fitbit to monitor their physical activity despite only 55% agreeing that it was easy to use and 65% that its use was motivational. Participants indicated increased confidence for physical activity after 12 months; 90% of whom stated that they felt confident continuing with physical activity after the trial. Outcome: The PACE-HD intervention was acceptable to HD participants and they felt supported by the intervention therapists. Knowledge gathered in this process evaluation can inform successful implementation, potential causal mechanisms and contextual factors that may affect intervention outcomes.